Gender-related factors affecting health seeking for neglected tropical diseases: findings from a qualitative study in Ethiopia. - Alexandra Wharton-Smith; Christian Rassi; Esey Batisso; Giuseppina Ortu; Rebecca King; Misganu Endriyas; Helen Counihan; Prudence Hamade; Dawit Getachew (Public Library of Science (PLoS), 2019)
BACKGROUND:Despite known gender-specific differences in terms of prevalence, transmission and exposure to neglected tropical diseases (NTDs), there is limited discussion of the influence of gender in NTD programmes and interventions. There is a paucity of research on how gender interacts with NTD service provision and uptake. This study, part of broader implementation research in Ethiopia, applied a gender lens to health seeking for five NTDs: lymphatic filariasis, podoconiosis, schistosomiasis, soil-transmitted helminth infection and trachoma. METHODOLOGY/PRINCIPAL FINDINGS:The study was conducted in a district of the Southern Nations, Nationalities, and Peoples' Region of Ethiopia where the five NTDs are prevalent. A qualitative methodology was adopted to explore participants' perspectives and experiences. Data generation methods included 20 interviews and four focus group discussions. Community members, volunteer Health Development Army leaders, Health Extension Workers and a range of health workers at the health post, health centre and hospital level (n = 59) were purposively sampled. Interviews and focus group discussions were audio recorded, transcribed verbatim into English then analysed through open coding, drawing on constant comparative methods. Gender related factors affected care seeking for NTDs and were described as reasons for not seeking care, delayed care seeking and treating NTDs with natural remedies. Women faced additional challenges in seeking health care due to gender inequalities and power dynamics in their domestic partnerships. Participants recommended raising community awareness about NTDs, however this remains problematic due to gender and social norms around appropriate discourse with members of the opposite gender. CONCLUSIONS/SIGNIFICANCE:The findings from this study provide crucial insights into how gender interacts with accessing health services, at different levels of the health system. If we are committed to leaving no one behind and achieving universal health coverage, it is essential to address gender disparities to access and utilisation of interventions delivered by national NTD programmes.